Ælred's Recrafting of the Life of Edward the Confessor - Yohe, Katherine (Cistercian studies quarterly, 2003)
Focuses on the prologue to the 'Life of Edward the Confessor' by &Aelig;lred of Rievaulx. Commitment of Edward to a simple lifestyle; Relationship of King Edward with allies; Canonization of the ruler.